Respuesta :

Answer:

a = - 6

Step-by-step explanation:

Given

f(x) = 3x + 5 , then

f(a) = 3a + 5 and f(a) = - 13 , then equating the right sides

3a + 5 = - 13 ( subtract 5 from both sides )

3a = - 18 ( divide both sides by 3 )

a = - 6

Answer:

a = -6

Step-by-step explanation:

see, x has been replaced by a.

so f(a) = 3a + 5 . . . . . . . (i)

a displaces x from it's every position in the equation.

and it's given that f(a) = -13

putting f(a) = -13 in equation (i) :-

3a + 5 = -13

  • taking like terms to one side

3a = -18

  • dividing the equation by 3

[tex] \blue{ \implies}\mathfrak { \red { \underline{ \: a = - 6 } } } [/tex]